Stochastic optimization of shape‐memory‐alloy rubber bearing (SMARB) for isolating buildings against random earthquake. Issue 9 (7th February 2014) - Gur, Sourav; Mishra, Sudib K.; Chakraborty, Subrata
SUMMARY Shape‐memory‐alloy (SMA) aided isolation bearing has been proposed recently in order to achieve improved performances in several aspects, comparing the traditional bearings for isolation. The behavior of such system has been experimentally demonstrated and numerically simulated under recorded seismic ground motions. The present work deals with the study of optimum performance of SMA‐based isolation system under random earthquake. The stochastic response evaluation of the isolated building is performed by nonlinear random vibration analysis via stochastic linearization of load‐deformation hysteresis of SMA. The behavior of the stochastic responses indicates the existence of optimal value of transformation strength of SMA to minimize the superstructure acceleration and thereby most efficient isolation. Thus, a stochastic structural optimization problem is taken up in order to obtain the optimal transformation strength. A closed form expression of such optimal parameters are also presented, which may be used for establishing an initial design. The viability of the optimization study is justified by analyzing the response of the optimal system under set of real earthquake ground motion records. The stochastic response behavior of the optimal system is found to be consistent with the responses obtained under real earthquake motions. Copyright © 2014 John Wiley & Sons, Ltd.